The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/mcn.12298
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the influence of inflammation on retinol‐binding protein in a population survey of Liberian preschool‐age children

Abstract: Vitamin A deficiency (VAD) is an important contributor to child morbidity and mortality. The prevalence of VAD, measured by retinol-binding protein (RBP) or retinol, is overestimated in populations with a high prevalence of inflammation. We aimed to quantify and adjust for the effect of inflammation on VAD prevalence in a nationally representative survey of Liberian children 6 to 35 months of age. We compared five approaches to adjust RBP for inflammation and estimate VAD prevalence (defined as RBP <0.7 μmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 23 publications
3
33
1
Order By: Relevance
“…These inflammation markers will assist in interpreting low ROH values [91]. Various adjustment approaches exist [92,93], and there is a growing consensus that VAD should only be estimated once ROH or RBP are adjusted using both C-reactive protein and alpha 1-acid glycoprotein. Despite these obstacles, micronutrient surveys have been successfully undertaken in countries with poor road infrastructure, limited electricity networks, and only basic laboratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammation markers will assist in interpreting low ROH values [91]. Various adjustment approaches exist [92,93], and there is a growing consensus that VAD should only be estimated once ROH or RBP are adjusted using both C-reactive protein and alpha 1-acid glycoprotein. Despite these obstacles, micronutrient surveys have been successfully undertaken in countries with poor road infrastructure, limited electricity networks, and only basic laboratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate, linear regression approach for adjusting IIH has recently been proposed. 16,35 The advantage of this approach is that it estimates context-specific adjustment factors, based on observed associations between specific nutritional biomarkers and the acute phase reactants, as opposed to using predefined cut-offs for inflammation. However, this approach has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the problem of overadjustment, Larson et al suggested that adjustment factors be applied to individuals at or above the first decile of the lognormalized AGP and CRP concentrations, as opposed to every individual. 16 Had we adopted this approach, we would have adjusted the retinol concentrations in over 90% of our study population. Such a procedure, which would imply that nearly all children have some degree of IIH, may be unjustifiable, even in regions with a high burden of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 This risk can be assessed by measuring dietary VA intakes or biological indicators of VA stores, which is discussed further in paper 3 of this series. Excessive VA intakes are generally defined by consumption greater than the tolerable upper intake level (UL).…”
Section: Safety Of Vitamin a Programsmentioning
confidence: 99%